Súcasné názory na etiopatogenézu preeklampsie - Homzová, M; Ostró, A (Ceska gynekologie, 2001)
OBJECTIVE: To present a review of literature and to present our experiences of patients with preeclampsia. DESIGN: Review article. SETTING: Second Clinic of Gynecology and Obstetrics, Medical Faculty of the Safarik University and L. Pasteur's Hospital, Kosice, Slovak Republic. METHODS: Compilation of data from scientific literature. RESULTS AND CONCLUSION: The etiology of preeclampsia is still unknown. The 4 hypotheses currently accepted are the placental ischemia hypothesis, genetic hypothesis, the immune maladaption and hypothesis of the imbalance between free oxygen radicals and scavengers in favor of oxidants. At the present is most popular the theory of oxidative stress, that lead to increased production of lipide peroxides, tromboxane A2 and decreased level of prostacyclin. This imbalance triggers endothelial dysfunction and its clinical manifestation. Scavenging antioxidants have protective effect in this process.
Keywords: ženské pohlaví; Humans; Pregnancy; Female; těhotenství; Pre-Eclampsia; preeklampsie; lidé